Judicial Discretion and Ultra Petita in Employment Termination Cases: Lessons from Dutch Arbitration System - Sabur, Laode Muhammad; Razak, Abdul; Halim, Hamzah; Jamhur (Hasanuddin Law Review, 2025)
The principle of ex aequo et bono occupies a unique position within Indonesia’s legal landscape: although not expressly codified, it is increasingly invoked by judges to pursue substantive justice in employment termination disputes. This judicial practice, however, raises concerns regarding legal certainty and the boundaries of judicial authority, especially when decisions extend beyond the parties’ claims and risk violating the ultra petita doctrine. This article examines the application of ex aequo et bono in Indonesian labor courts through a normative legal analysis, using both comparative and conceptual approaches. A focal point of the study is Supreme Court Decision No. 223 K/Pdt.Sus-PHI/2017, in which the court terminated an employment relationship despite neither party explicitly requesting such relief. By comparing Indonesia’s judicial approach with the Netherlands, where ex aequo et bono is permitted exclusively within arbitration and only with explicit party consent. This article highlights the structural safeguards embedded in Dutch law that preserve both fairness and legal certainty. The results show that Indonesia’s unregulated use of ex aequo et bono creates inconsistencies and risks judicial overreach, underscoring the urgent need for statutory guidance. This study argues that incorporating explicit party consent and clearer procedural boundaries into Indonesia’s labor dispute resolution framework would better harmonize equity-based reasoning with the principles of legal certainty and judicial accountability.